The story of Wolverine - Teitelbaum, Michael (New York : DK, 2009)
"Discover how a frail and sickly child grew claws, ran wild with wolves, and became the super hero Wolverine!"--P. [4] of cover.
Introduction -- Early days -- Logan the drifter -- Weapon X -- Joining the X-men -- Wolverine's abilities -- Professor X -- Jean Grey -- Rogue -- Nightcrawler -- Alpha flight -- New avengers -- Nick Fury and S.H.I.E.L.D. -- Sabretooth -- Magneto -- Hulk -- Silver samurai -- Juggernaut -- Apocalypse -- Hulk and Wendigo -- Wolverine vs. Sabretooth -- Trials of Wolverine.
Includes index.